2008
DOI: 10.1177/1352458508089228
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of four different assays for the detection of binding antibodies against interferon-β

Abstract: We conclude that the cELISA seems to be most suitable for NAB screening, but BAB titers cannot reliably predict NAB titers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The BAb cut-off titer might also vary, depending upon the assay used. Although previous studies found fair inter-and intra-assay variability in terms of BAb frequency, 19,34 there are some hints that BAb titers differ between the different immunoassays. 19 The chosen time point for blood collection of 4-12 hours after the last IFN-b injection seemed appropriate, as previous studies show that different IFN-b-gene products are already induced after 3 hours and peak around 12 hours.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The BAb cut-off titer might also vary, depending upon the assay used. Although previous studies found fair inter-and intra-assay variability in terms of BAb frequency, 19,34 there are some hints that BAb titers differ between the different immunoassays. 19 The chosen time point for blood collection of 4-12 hours after the last IFN-b injection seemed appropriate, as previous studies show that different IFN-b-gene products are already induced after 3 hours and peak around 12 hours.…”
Section: Discussionmentioning
confidence: 81%
“…Although previous studies found fair inter-and intra-assay variability in terms of BAb frequency, 19,34 there are some hints that BAb titers differ between the different immunoassays. 19 The chosen time point for blood collection of 4-12 hours after the last IFN-b injection seemed appropriate, as previous studies show that different IFN-b-gene products are already induced after 3 hours and peak around 12 hours. 12,20,28 We want to stress that this investigation was not intended to study the impact of anti-IFN-b antibodies on clinical outcome parameters.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Measurement of BAbs by Western blotting [Gneiss et al 2008] involves the separation of the IFNβ by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) followed by transfer onto a nitrocellulose membrane. Membrane strips are incubated with diluted patient serum, a positive control (mouse anti-IFNβ) and a negative control.…”
Section: Testing Binding Antibodies and Neutralizing Antibodies In Thmentioning
confidence: 99%
“…The most commonly used method for measuring of BAbs is ELISA [10,17], particularly capture ELISA, which correlates better with NAb titers than does direct ELISA [18]. In general, ELISA titers correlate only weakly with NAb titers, but BAb-negative samples measured by ELISA reliably predict NAb-negativity [19].…”
Section: Introductionmentioning
confidence: 99%